Diseño del curso en línea: trabajo interdisciplinario - Salas Soto, Silvia Elena (2008)
The intention of this article is to offer to the on-line course designers elements to consider in the elaboration of this type of courses, since this one is a task that involves contributions in three dimensions: the programming of the platform that assumes technological functions; the preparation of the on-line course that requires educative and curricular fundaments and putting in practice the course that is mediated by a tutor or facilitator. The work is organized in four sections: first one is related to the thematic of the virtual campus, its functions and characteristics, especially to the concept of virtual campus and the use that has been given to this tool. A second section corresponds to the design of the on-line course, which presents information about virtual environments of learning. The third one describes elements of the programming of the platform in correspondence with the on-line design of the course and finally, the fourth subject offers guidelines for the tutor to mediate the on-line course. The information is sustained from the theoretical perspective by studies in this field like Area (2001), Herrera (2006 ), Cenich (2005), Kanuka (2005), Juarez (2003 ), Picciano (2002), Anderson (2001), Barberà (2001), Cabero (2000) y Dorado (1996).